PENGARUH LEVERAGE DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA DENGAN AGENCY COST SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR - Rahyuningsih Rahyuningsih; Sri Ayem (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to compare the leverage and managerial ownership of earnings management with agency cost as an intervening variable. This study took a population of several companies listed on IDX and the number of samples in this study were 16 companies, the sample technique used was purposive sampling. The data analysis method used is the path analysis. The results of this study after testing the first stage showed simultaneously that leverage and managerial ownership affect agency cost and testing the second stage of leverage, managerial ownership and agency cost affect earnings management. Partially through the t test, in the first stage of testing that leverage affects agency cost and managerial ownership does not affect agency cost. The second stage of testing that leverage does not affect earnings management, managerial ownership does not affect earnings management and agency costs affect earnings management.